2020
DOI: 10.1002/iid3.391
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation initiates a vicious cycle between obesity and nonalcoholic fatty liver disease

Abstract: Low‐level of chronic inflammation activation is characteristic of obesity. Nonalcoholic fatty liver disease (NAFLD) is closely linked to obesity and is an emerging health problem, it originates from abnormal accumulation of triglycerides in the liver, and sometimes causes inflammatory reactions that could contribute to cirrhosis and liver cancer, thus its pathogenesis needs to be clarified for more treatment options. Once NAFLD is established, it contributes to systemic inflammation, the low‐grade inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 140 publications
(134 reference statements)
0
40
0
Order By: Relevance
“…NAFLD is a low-grade inflammatory chronic disease that the process of its occurrence and progression is accelerated by the high level of pro-inflammatory cytokines, including Interleukin‐1, TNF‐α, and Interleukin‐6 and the high level secretion of adipokines. These inflammatory factors trigger various processes, including lipotoxicity, hepatocyte cell death, liver inflammation, fibrosis, and pathological angiogenesis [ 39 ]. Therefore, any environmental factor affecting the creation or exacerbation of inflammatory conditions, such as greater adherence to a pro-inflammatory dietary pattern, which is associated with increased cellular or serum levels of these inflammatory markers, can increase the risk of fatty liver disease or its progression.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD is a low-grade inflammatory chronic disease that the process of its occurrence and progression is accelerated by the high level of pro-inflammatory cytokines, including Interleukin‐1, TNF‐α, and Interleukin‐6 and the high level secretion of adipokines. These inflammatory factors trigger various processes, including lipotoxicity, hepatocyte cell death, liver inflammation, fibrosis, and pathological angiogenesis [ 39 ]. Therefore, any environmental factor affecting the creation or exacerbation of inflammatory conditions, such as greater adherence to a pro-inflammatory dietary pattern, which is associated with increased cellular or serum levels of these inflammatory markers, can increase the risk of fatty liver disease or its progression.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD is involved in chronic and low-grade inflammation ( Luo and Lin, 2020 ). This study showed that IsA treatment improved liver injury and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a health problem, and nonalcoholic fatty liver (NAFLD) is a common ailment belonged to obesity. It is characterized by the accumulation of fat in the liver cells, and the hepatocytes [36]. The latest evidence has shown that phenolic compounds can enhance the absorption of nutrients, lipid metabolism, and weight loss [37].…”
Section: Bee Pollen Prevents Obesity and Combats Liver Disordersmentioning
confidence: 99%